2018
DOI: 10.1155/2018/6071826
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between miR-200 Family Overexpression and Cancer Prognosis

Abstract: The correlation between miR-200 family overexpression and cancer prognosis remains controversial. Therefore, we conducted a systematic review and meta-analysis by searching PubMed, Embase, Cochrane Library, China Biology Medicine disc (CBM), and China National Knowledge Infrastructure (CNKI) to identify eligible studies. Hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated to evaluate the strength of the correlations. Additionally, different subgroup analyses and publication bias test were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Reliable biomarkers are thus needed to facilitate early diagnosis and to optimize the different therapies for individual patients [ 138 ]. To this end, several studies investigated the possible role of miR-200 as novel diagnostic tools in NSCLC (reviewed in [ 139 ]).…”
Section: Circulating Mir-200 As Biomarkersmentioning
confidence: 99%
“…Reliable biomarkers are thus needed to facilitate early diagnosis and to optimize the different therapies for individual patients [ 138 ]. To this end, several studies investigated the possible role of miR-200 as novel diagnostic tools in NSCLC (reviewed in [ 139 ]).…”
Section: Circulating Mir-200 As Biomarkersmentioning
confidence: 99%
“…Moreover, we found that bile exosomal miR-200a-3p, miR-200c-3p, and serum exosomal miR-200c-3p were not only diagnostic biomarkers but also signs representing unfavorable patients’ survival, closely associated with tumor stage and tumor differentiation. Plenty of published articles showed that higher expression of miR-200 family was related to worse survival outcomes for cancer patients ( 7 , 25 ). It was reported in a meta-analysis that miR-200 expression was negatively associated with survival prognosis in all cancers combined, especially in lung and breast cancer ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the miR-200 family members are regarded as epithelial markers that inhibit the EMT process by directly targeting several EMT-associated genes including ZEB1 and ZEB2 [ 22 , 40 ], and the upregulation of miR-200 family members is related to the promotion of the mesenchymal-to-epithelial transition (MET) process [ 41 ]. In contrast, accumulative data have revealed the oncogenic functions of the miR-200 family, whose members are upregulated in several cancers and are associated with poor clinical outcomes [ 42 , 43 ], suggesting a dual role for the miR-200 family in tumorigenesis. Indeed, miR-141 has been widely considered a promising biomarker for a variety of cancers, such as non-small cell lung cancer [ 44 ], colorectal cancer [ 45 ] and prostate cancer [ 46 ], and miR-141 levels are correlated with tumor metastatic progression and poor patient prognosis [ 27 , 47 49 ].…”
Section: Discussionmentioning
confidence: 99%